MENGEMBANGKAN SKILL MENGHITUNG ANAK MELALUI PROGRAM ASMAUL HUSNA ARITHMETIC DI YAYASAN NURUL MUSTHOFA - Faizatul Badriyah; Ulfiani (Kalam Nusantara Institute, 2023)
A learning system that is very efficient and has logicality above the intellect of ordinary humans who use the right brain, this program is called AHA where 10 fingers become 99 fingers and the way of thinking uses the right brain. Programs that are rarely used elsewhere. The AHA program really helps students to think clearly, quickly, and precisely. So that students can count in an easier way. With this method it is hoped that it can inspire other students to use the AHA method in learning. The AHA (Asmaul Husna Arithmetic) program provides a slightly different alternative way of counting for golden age children (0 to 8 years) who are actually hungry for other ways of counting. However, his teaching uses only one method of counting. And this method only represents the child's logical-mathematical intelligence. In this case, the method is further expanded with visual and kinesthetic special intelligence. The diversity of elements of intelligence is what provokes children to like learning activities called counting. Can more easily teach how to count to students while making it easier to introduce asmaul husna, so that students know and understand the contents contained therein.